SURAU DAN PESANTREN SEBAGAI LEMBAGA PENGEMBANG MASYARAKAT ISLAM DI INDONESIA (KAJIAN PERSPEKTIF HISTORIS) - Furqan, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
As an old legacy, the function of the mosque in Minangkabau has gradually developed. At first surau functioned as a place for traditional ceremonies, then developed into a place of worship and gathering of young people to learn various knowledge and skills. In addition, adult men who are not married or who have been widowers make surau as a place to rest at night. This means that the mosque at that time had a dual role, in addition to being an educational institution as well as a social institution. During a time of change, the education system does not only provide a study of the Qur'an and the study of books and orders. But it has been added to the teaching of a number of religious literature such as the book of jurisprudence, nahwu, sharaf and Sufism. Judging from the history of the emergence of pesantren and madrasa in Indonesia, pesantren first appeared compared to madrasa. This means that the education process in pesantren can be said to be the parent of the current developing education process. From the beginning, the more dominant pesantren curriculum was related to religious lessons sourced from Arabic yellow books. Whereas general lessons are hardly studied at all. But along with the demands of the times, there are already some pesantren that incorporate general lessons into their curriculum, so that modern pesantren are born which seek to integrate religious and general knowledge into their curriculum. In addition, the pesantren curriculum also seeks to equip its students with various life skills as capital to enter the community after they have completed their education at the pesantren. The role and existence of the surau and Islamic boarding school as one of the original Indonesian community development institutions must indeed be preserved and monitored for its development, because the presence of the surau and Islamic boarding school in the midst of the community is in addition to empowering the community as well as a forum to prepare capable Ulama cadres mastering and understanding the Qur'an and al-Hadith properly and correctly and in accordance with the needs of the community.Keywords: Surau, Islamic Boarding School, Islamic Community Development.